Porous silicon mass spectrometry as an alternative confirmatory assay for compliance testing of methadone. Issue 5 (1st August 2016) - Guinan, Taryn M.; Neldner, Declan; Stockham, Peter; Kobus, Hilton; Della Vedova, Christopher B.; Voelcker, Nicolas H.
Abstract : Porous silicon based surface‐assisted laser desorption ionization mass spectrometry (pSi SALDI‐MS) is an analytical technique well suited for high throughput analysis of low molecular weight compounds from biological samples. A potential application of this technology is the compliance monitoring of opioid addiction programmes, where methadone is used as a pharmacological treatment for drugs such as heroin. Here, we present the detection and quantification of methadone and 2‐ethylidene‐1, 5‐dimethyl‐3, 3‐diphenylpyrrolidine (EDDP) from water and clinical samples (saliva, urine, and plasma) from opioid dependent participants using pSi SALDI‐MS. A one‐step solvent phase extraction using chloroform was developed for the detection of methadone from clinical samples for analysis by pSi SALDI‐MS. Liquid chromatography‐mass spectrometry (LC‐MS) was used as a comparative technique for the quantification of methadone from clinical saliva and plasma samples. In all cases, we obtained a good correlation of pSi SALDI‐MS and LC‐MS results, suggesting that pSi SALDI‐MS may be an alternative procedure for high‐throughput screening and quantification for application in opioid compliance testing. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Surface‐assisted laser desorption/ionization (SALDI) mass spectrometry on porous silicon was used for the detection and quantification of methadone from clinical saliva, urine and plasma samples. The presence of methamphetamine and nicotine could be detected simultaneously to methadone in these clinical samples. SALDI mass spectrometry with porous silicon gave results comparable to liquid chromatography mass spectrometry.